A social coding based refinement strategy for data on the Web - dos Santos, Helton Douglas A.; Oliveira, Marcelo Iury S.; Lóscio, Bernadette Farias (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2018)
Dataset refinement is a primary activity mainly related to data cleansing and enrichment. Usually, refinement is performed by publishers, although consumers often clean and enrich datasets in their consumption activities. However, in general, consumer's effort is lost, since most times the result of the refinement is not shared back with the publisher or other consumers. In this context, this work proposes a refinement strategy based on the principles of social coding to allow the refinement of datasets published on the Web in a collaborative way.